2013
DOI: 10.1093/jxb/ert390
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the microtubule network alters cellulose deposition and causes major changes in pectin distribution in the cell wall of the green alga,Penium margaritaceum

Abstract: Application of the dintroaniline compound, oryzalin, which inhibits microtubule formation, to the unicellular green alga Penium margaritaceum caused major perturbations to its cell morphology, such as swelling at the wall expansion zone in the central isthmus region. Cell wall structure was also notably altered, including a thinning of the inner cellulosic wall layer and a major disruption of the homogalacturonan (HG)-rich outer wall layer lattice. Polysaccharide microarray analysis indicated that the oryzalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
(89 reference statements)
3
16
1
Order By: Relevance
“…Pectin vesicles were observed in close association with cortical MTs near the mucilage secretion pockets during Arabidopsis seed coat development ( McFarlane et al , 2008 ). Oryzalin treatment was shown to affect not only cellulose but also pectin deposition in unicellular green alga ( Domozych et al , 2014 ). Two recent studies showed that Arabidopsis mutants defective in kinesin motor proteins exhibited abnormal Golgi morphology, with altered pectin secretions and accumulation of arabinose-containing carbohydrates in the cell wall ( Kong et al , 2015 ; Zhu et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pectin vesicles were observed in close association with cortical MTs near the mucilage secretion pockets during Arabidopsis seed coat development ( McFarlane et al , 2008 ). Oryzalin treatment was shown to affect not only cellulose but also pectin deposition in unicellular green alga ( Domozych et al , 2014 ). Two recent studies showed that Arabidopsis mutants defective in kinesin motor proteins exhibited abnormal Golgi morphology, with altered pectin secretions and accumulation of arabinose-containing carbohydrates in the cell wall ( Kong et al , 2015 ; Zhu et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the MT–MF alignment by cobtorin in tobacco BY-2 cells altered pectin distribution, which implicated not only pectins in MT–MF alignment, but also MTs in pectin deposition ( Yoneda et al , 2010 ). Similarly, depolymerization of MTs by oryzalin affected not only cellulose but also pectin deposition in Penium margaritaceum ( Domozych et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…After testing several enzymes, we determined that only a mixture of cellulase and PL yielded protoplasts. PL catalyzes HG by β-elimination of (1 → 4)-α-d-galacturonan [30], and it has been reported to remove the HG-rich OL that forms the outer lattice in Penium [15,18]. Our results show that only PL, acting at the OL level of the cell wall, combined with cellulase, acting at the IL level, were sufficient to compromised wall integrity at the isthmus in order to release the protoplast.…”
Section: Cell Walls Without the Hg Lattice Are Not Compromised To Yiementioning
confidence: 65%
“…Finally, recent molecular investigations [16] are providing new insights and creating opportunities for studying Penium as a model for plant cell physiology, development and evolution. All of these features make Penium an outstanding experimental system in plant cell biology [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the desmid, Penium margaritaceum, a band of cortical microtubules found in the central pre-division expansion zone is arranged in the same orientation as that of the innermost layer of cellulose microfibrils (Ochs et al 2014). If the microtubules are altered using pharmacological agents (e.g., oryzalin), cellulose microfibril production is altered and the localized swelling of the cell occurs (Domozych et al 2014b). This cortical microtubule band also serves a "marker" for expansion prior to cell division, i.e., similar to a pre-prophase band.…”
mentioning
confidence: 99%